Challenges experienced by learners during assessment with the use of English as language of teaching and learning history - Rapetsoa, Johannah Mapotlakishe (University of Limpopo (Turfloop Campus), 2011)
This dissertation investigates the challenges that history learners in rural black schools are faced with during examinations with the use of English as a language of learning and teaching. The aim of the research is to investigate whether English, which is used as a language of learning and teaching in schools, is a barrier to the learning and teaching of history. It is believed that the use of English has implications on the results that learners obtain during summative assessment. The literature revealed that any language of learning and teaching, which is not the mother tongue of learners, has an impact on the process of learning. Assessment, which determines whether the learning outcomes have been attained or not, is affected by factors such as the type of assessment, for example, formative or summative, the purpose of assessment and the rules and regulations that go along with assessment. In order to gain a greater insight and comprehensive understanding of the research problem, that is, the challenges that are faced by learners during summative assessment, both the qualitative and quantitative approaches were used. A case study design was adopted. The research techniques employed were interviews, document analyses and observations. The findings indicated that the environment in which the learners are learning second language has impact on the learners’ language proficiency. They further indicate that assessment in itself poses challenge to learners, in addition to the challenges caused by the language barriers. It was also indicated that the educators and the learners prefer to use English as the language of learning and teaching, despite all the challenges they face when they use English. The important findings were discussed with the aim of arriving at conclusions, shortcomings recommendations.
Thesis (M.Ed. (Language Education)) --University of Limpopo, 2011
Keywords: Language and learning; Learning and teaching; 372.6521; English language -- Study and teaching; Language and education -- South Africa